Formatting the moral imperatives of modern youth in the conditions of post-industrial society (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the analysis of the phenomenology ofthe moral and psychological development of the individual in the modernconditions of the post-industrial society. It is stated that the formatting ofthe system of moral imperatives of modern youth is due to changes in thesocial space of public life; what has been said prompts the determinationof trends in the assimilation of moral imperatives by young people inorder to further optimize them. The article highlights the specific trendsin the moral development of youth in an unstable information society. Theemphasis is made on the humanistic and liberal views of philosophers onthe peculiarities of the development of the moral properties of a person.beginquote
Keywords: morality; moral imperatives; youth; humanistic and liberal traditions; socio-cultural space